Risk factors of role stress and professional burnout among nurse anesthetists: A multicenter cross‐sectional study. Issue 3 (7th March 2021) - Meng, Haihong; Bai, Shuling; Cao, Qinqin
Abstract: Background: In China, there is no unified standard for the responsibilities and authority of nurse anesthetists, resulting in different professional expectations from anesthesiologists and nursing managers, which may result in high levels of role stress and burnout in nurse anesthetists. Additional factors such as high occupational risk and heavy work may also contribute to role stress and burnout. Methods: In this multicenter cross‐sectional study, an online questionnaire survey was conducted among 198 nurses from six tertiary hospitals in Shandong Province. The t test, analysis of variance, linear regression, and logistic regression were used to analyze the risk factors for role stress and professional burnout. Results: The scores of role conflict and role ambiguity in role stress were 30.61 ± 9.53 and 31.89 ± 9.56, respectively; satisfaction with income and the working environment, the hospital's attention, years of experience as a nurse, clarity concerning the nurse anesthetist's occupational scope, and attitude to career prospects were independent risk factors for role stress. The burnout data were non‐normally distributed and were expressed as medians and quartiles. The scores of emotional exhaustion, depersonalization, and personal achievement in professional burnout were 30 (26–34), 11 (8–14), and 23 (20–26) respectively. The number of working hours per week, attitude to career prospects, satisfaction with the working environment and income, physical health, gender, and education were independent risk factors for burnout. Conclusions: Chinese nurse anesthetists were found to be in danger of high role stress and professional burnout, a situation requiring the attention of managers.